1112 Evaluating the clinical utility of ASOT in West London: a retrospective study. (17th August 2022) - Whittaker, Elizabeth; Kwiatkowska, Zofia; Goel, Akshit
Abstract : Aims: Antistreptolysin O titre (ASOT) is used to confirm Group A Streptococcus (GAS) infection and screen for post-streptococcal complications. Establishing its clinically useful upper limit of normal (ULN) is challenging and there is currently limited evidence to guide interpretation of ULN in low-risk populations such as West London. The objective of this study was to establish the usefulness of ASOT as a screening and diagnostic tool to guide diagnosis and management of children presenting with fever, and to evaluate the utility of the currently used ULN of 200IU/mL. Methods: Positive ASOT results were extracted from North West London Pathology for the study period. Clinical data (demographics, presenting features, investigation results, diagnosis and management) was extracted from electronic patient records. Duplicate and inaccessible patient records were excluded. Only patients <21 years of age were included. Associations and correlations between clinical features, results and diagnoses were examined using GraphPad Prism. Results: 154 patients were included in the study, with 51% males. The mean age of patients in this study was 9.75 (range 1.0-20.5 years). We found no significant association between combinations of presenting symptoms (haematuria, arthralgia, lymphadenopathy, rash, throat involvement, pyrexia) and a positive ASOT, suggesting that a conclusive diagnosis cannot be made on this basis alone. The odds of having a GAS infection were higher for an elevated white cell count (WCC) (odds ratio (OR), 3.40; 95% confidence interval (CI), 1.35–8.53), raised neutrophil count (OR, 5.05; 95%CI, 1.73–14.72), raised erythrocyte sedimentation rate (OR, 3.0; 95%CI, 0.99–9.10) and low albumin (OR, 2.9; 95%CI, 1.17–7.19). A wide range of diagnoses were identified ( figure 1 ). Common childhood illnesses including viral infections and allergies were present, in addition to GAS-related pathologies. In particular, Kawasaki disease and HSP were difficult to differentiate clinically and were more common than expected. Higher ASOT values were uncommon (>1600IU/mL=10/144, 6.9%) and they were associated with high proportions of GAS-related diagnoses ( figure 2 ). ASOT >1600IU/mL is strongly associated with GAS, but the test is non-specific at lower values. 28.6% (n=14) of patients with ASOT of 200-400IU/mL had GAS involvement. Consequently, increasing the ULN to 400IU/mL could result in missed diagnoses. Conclusion: At higher ASOT values, there is a strong suspicion for GAS involvement; this assertion is limited by low sample size. Although ASOT is less specific at lower titres, the current ULN (200IU/mL) does correctly identify GAS involvement in a considerable number of individuals. The test has a 'rule-out' diagnostic value for conditions presenting with highly non-specific symptoThe diagnostic accuracy may be improved when using other biomarkers in combination with ASOT. Furthermore, it would be of value to develop an algorithm to test this on a larger cohort.